Circadian changes in thyroid hormones of piau, Leporinus obtusidens Valenciennes, 1847 (Osteichthyes, Anostomidae) after feeding - DOI: 10.4025/actascibiolsci.v31i4.5814 - Walter Dias Junior; Lea Rosa Mourgués-Schurter (Acta Scientiarum. Biological Sciences, 2009)
To evaluate circadian changes in thyroid hormones of piau, Leporinus obtusidens Valenciennes, 1847, (Osteichthyes, Anostomidae) after feeding were determined the plasma levels of thyroid hormones (TH) of 128 fishes, same age, immature, both sexes, distributed into four classes of weight. They were kept in 16 aquaria (100 L), with artificial aeration and 2 L min. -1 water flow, from March to August, 1996, in Aquaculture Station of the Universidade Federal de Lavras (UFLA). Daily, feed was supplied at 5% body weight. For blood samples, the fishes were anesthetized with benzocaine 10%, and plasmatic levels of TH were determined at 1, 4, 7, 10, 13, 16 and 22h after food supply during 4 consecutive days in June and in August, period of lowest temperature. The classes of weight 63, 75, 82 and 91 g were considered homogeneous, showing that plasmatic concentrations of T3 and T4 were body weight independent for this fish species. The daily cycle of plasma TH were correlated with feed intake, reaching the highest levels 7 h after feeding supply (T3 = 1.75 ± 0.07 ng mL-1 and T4 = 14.9 ± 1.59 ng mL-1). It was also possible to verify that the daily intake is directly correlated with water temperature which is affected by day-light cycle